2019
DOI: 10.1371/journal.pone.0214998
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing emotional Stroop interference in posttraumatic stress disorder, major depression and anxiety disorders: A systematic review and meta-analysis

Abstract: Background Posttraumatic stress disorder is a debilitating psychiatric disorder characterized by symptoms of intrusive re-experiencing of trauma, avoidance and hyper-arousal. Diagnosis and treatment of PTSD is further complicated by concurrently occurring disorders, the most frequent being major depressive disorder and anxiety disorders. Previous research highlights that attentional processing in posttraumatic stress disorder is associated with substantial interference by emotional stimuli, a phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 108 publications
1
31
0
1
Order By: Relevance
“…13 There is also evidence of increased response latencies to both anxiety-related words and generally negative words when using emotional Stroop (eStroop) tasks across anxiety disorders, suggesting an attentional bias toward threat-related stimuli. 14 In younger adults, changes in emotion processing similar to those in other anxiety disorders have also been seen in Post-Traumatic Stress Disorder (PTSD). For example, a meta-analysis of eStroop task performance in PTSD 15 found that individuals with PTSD, compared with healthy controls, showed impairments in the eStroop task when processing trauma-related and generally threatening, but not positive, information.…”
Section: Emotion Processing In Anxietymentioning
confidence: 99%
“…13 There is also evidence of increased response latencies to both anxiety-related words and generally negative words when using emotional Stroop (eStroop) tasks across anxiety disorders, suggesting an attentional bias toward threat-related stimuli. 14 In younger adults, changes in emotion processing similar to those in other anxiety disorders have also been seen in Post-Traumatic Stress Disorder (PTSD). For example, a meta-analysis of eStroop task performance in PTSD 15 found that individuals with PTSD, compared with healthy controls, showed impairments in the eStroop task when processing trauma-related and generally threatening, but not positive, information.…”
Section: Emotion Processing In Anxietymentioning
confidence: 99%
“…The severity of dementia was not ascertained by the Clinical Dementia Rating (CDR) scale, cognitive function by the Mini Mental State Examination (MMSE) or neuroimaging findings with magnetic resonance imaging/PET. We recommend that the Stroop score, as a generic defense response [ 63 ], concurring with chronic stress [ 64 ] may have dual advantages both as a stress test and as an early T3D dementia risk marker.…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between slower color naming of trauma-relevant words and PTSD is more reliable, the relationship between trauma-irrelevant negative words and PTSD is less reliable and has not survived meta-analytic investigation (Joyal et al, 2019). Indeed, PTSD is characterized not only by "capture" of attention by trauma-related stimuli typically assessed in divided attention paradigms but also by greater vigilance for threatening information (Kimble et al, 2014) and difficulty disengaging attention from trauma-related words (El Khoury-Malhame et al, 2011;Pineles, Shipherd, Mostoufi, Abramovitz, & Yovel, 2009;Pineles, Shipherd, Welch, Yovel, 2007), suggesting the need for using more paradigms where threatening or negative stimuli are task-relevant and the target of attention.…”
Section: Attention and Memory Biases In Ptsdmentioning
confidence: 99%